The Influence of Pedagogical Competence and Organizational Support on Teacher Performance - Ningsih, Sri; Sukardi, Sukardi (Untag Business and Accounting Review, 2023)
This research aimed to determine the influence of pedagogical competence and organizational support on teacher performance. Using census techniques, the sample in the research was all teachers at SMK Negeri 1 Kandeman, Batang, Central Java, Indonesia, with totaling 80 respondent. The data source in this research is primary data collected using questionnaires. The data analysis used linear multiple regression analysis. The results of the analysis show that pedagogical competence and organizational support have a significant positive effect on teacher performance. This research implies that the central and regional governments can improve the competence and welfare of teachers.